Comparative analysis on injury incidence and characteristics in men's collegiate athletes between combat and ball sports - Choi, E.-H.; Han, M.-O.; Jun, H.-P. (Exercise Science, 2024)
PURPOSE: To identify the characteristics of injuries among male collegiate athletes in combat and ball sports during the 2021 season and to propose strategies for injury prevention. METHODS: A total of 143 participants (67 combat and 76 ball sports athletes) registered with the Korean Sports & Olympic Committee in 2021 participated in this study. Each athlete responded to a questionnaire based on the injury survey developed by the International Olympic Committee. The questionnaire collected information on four demographic characteristics and three aspects of sports injuries: injury location, type, and cause. The Chi-squared test was used to compare injuries and determine the association between the two types of sports. RESULTS: The practice injuries and athlete exposures (AEs) recorded were 328 and 141,076 in combat sports and 384 and 142,054 in ball sports, respectively. The injury incidence rates (IRs) were 2.14/1,000 AEs (95% confidence interval [CI], 1.89-2.39) and 2.02/1,000 AEs (95% CI, 1.75-2.29) in combat and ball sports, respectively. Furthermore, the most common location, type, and cause of injury associated with both combat and ball sports were the ankles (combat: n=105, 34.8%; ball: n=60, 20.9%), sprain/ligamentous ruptures (combat: n=83, 26.4%; ball: n=96, 28.3%), and overtraining (combat: n=133, 41.7%; ball: n=94, 27.3%), respectively. Combat and ball sports were significantly associated in terms of injury location (Chi-squared =334.771, p<.001), type (Chi-squared=205.099, p<.001), and cause (Chi-squared=40.278, p<.05). CONCLUSIONS: Based on the results of this study, implementing an injury surveillance system is crucial for identifying risk factors and developing strategies to prevent injuries in both combat and ball sports. Additionally, coaches, supervisors, and trainers can incorporate specific exercise programs into their training regimens to strengthen anatomy frequently affected by injuries.